Cognitive therapy for post-traumatic stress disorder following critical illness and intensive care unit admission. (2020) - Murray, Hannah; Grey, Nick; Wild, Jennifer; Warnock-Parkes, Emma; Kerr, Alice; Clark, David M.; Ehlers, Anke
Abstract: Around a quarter of patients treated in intensive care units (ICUs) will develop symptoms of post-traumatic stress disorder (PTSD). Given the dramatic increase in ICU admissions during the COVID-19 pandemic, clinicians are likely to see a rise in post-ICU PTSD cases in the coming months. Post-ICU PTSD can present various challenges to clinicians, and no clinical guidelines have been published for delivering trauma-focused cognitive behavioural therapy with this population. In this article, we describe how to use cognitive therapy for PTSD (CT-PTSD), a first line treatment for PTSD recommended by the National Institute for Health and Care Excellence. Using clinical case examples, we outline the key techniques involved in CT-PTSD, and describe their application to treating patients with PTSD following ICU. Key learning aims: (1) To recognise PTSD following admissions to intensive care units (ICUs). (2) To understand how the ICU experience can lead to PTSD development. (3) To understand how Ehlers and Clark's (2000 ) cognitive model of PTSD can be applied to post-ICU PTSD. (4) To be able to apply cognitive therapy for PTSD to patients with post-ICU PTSD.